Morphological of Zinc Ferrite Nanostructure Using the Hydrothermal Synthesis - Kiki Rezki Lestari (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Over the last two decades, many methods for synthesizing various ZnFe2O4 nanostructures of uniform size and shape, such as nanospheres, nanoflowers, nanorods, and nanotubes, have been developed. It seems challenging to investigate a practical and cost-effective method to synthesize cubic ZnFe2O4 magnetite with cubic morphological properties in an aqueous solution. The morphology of zinc ferrite nanostructures is mostly random and non-uniform. The objective of this study is to create reasonably uniform single-crystal zinc ferrite nanocubes. The hydrothermal method was used to successfully sample zinc ferrite by varying the amount of (En) ethylenediamine (0 - 2.4 mL) in the solution. The outcomes demonstrated that the nanocubes, with a particle size of nearly 48 nm, had a more uniform morphology than other samples. The morphology and dimensions of the samples were examined using scanning electron microscopy in conjunction with energy dispersion X-ray spectroscopy.